Inspirasi Visual Peralatan Jahit Sebagai Pengembangan Motif Baru ‘’Unsur Prodi Busana’’ Melalui Batik Cap - Alin Rahma Saputri; Dian Retnasari (Fakultas Industri Kreatif Universitas Surabaya, 2025)
Stamped batik is a batik technique that is done with stamps made from wood, metal or paper. Stamped batik is in great demand because of the efficient way of making it, but does not eliminate the essential values of batik itself. Batik making does not only focus on the technique, various kinds of batik motifs become more varied and develop over time. The author focuses on developing new motifs in the process of making stamped batik by utilizing visual inspiration from sewing equipment. This research was carried out in order to enrich elements of the Fashion Study Program by integrating innovation in stamped batik production. It is hoped that this research can contribute to the development of new motifs in the world of stamped batik by utilizing visual inspiration from sewing equipment, as well as expanding understanding of design innovation